Cluster School of Excellence in collaboration with Universiti Malaysia Pahang on Malay Language Literacy - Juwairiah, Osman (2018)
Pekan, 17th October 2018- Primary and Secondary School Cluster Excellence in Malay Language has jointly collaborated with Universiti Malaysia Pahang (UMP), Pekan campus to organize a programme on Malay Language Literacy. The schools involved were SK Selancar 2, SK Bukit Lada and SMK Seri Bera, Pahang. Whereas, the departments UMP who had contributed towards the success of this program were the Department of Academic and International Affairs (JHEAA) and the Center for Modern and Human Language Sciences (CMLHS), UMP. The program was officiated by the Dean of the Center for Modern Languages and Human Sciences (CMLHS), UMP, Assoc. Prof. Dr. Muhammad Nubli Abd Wahab, also attended by the Deputy Dean of Academic Affairs, Dr. Munira Abdul Razak. This Malay language program conducted aimed at strengthening the teaching and learning of Malay language to school students and to provide exposure on the best activities in improving the performance of Malay language in schools.